PEMAHAMAN MASYARAKAT DESA UREK-UREK GONDANGLEGI MALANG TENTANG NAFKAH SUAMI TERHADAP PEREMPUAN BURUH MIGRAN - Rosa Afdania (Jurnal Penelitian Ilmiah INTAJ, 2024)
The research aims to explore the community's perspective on the role of women as migrant workers, the status of the property earned by wives, and the husband's financial obligation in the context of shifting gender roles. It employs a qualitative method with descriptive analysis to deeply explore personal experiences and perspectives regarding the financial obligations of husbands toward female migrant workers. The findings reveal that the community holds diverse views about female migrant workers. Their work is seen as a way to fulfill the family's economic needs, despite challenges such as separation and exploitation risks. Women's economic contributions are increasingly appreciated, although they sometimes conflict with traditional norms. The majority of the community recognizes that the income earned by wives is their personal property, in accordance with Islamic teachings. In financial management, a collaborative approach is often applied, although the husband’s financial obligation is still considered his primary responsibility. While women's role as breadwinners is increasingly acknowledged, the husband's role as the primary provider remains unchanged. This study highlights changes in gender roles within families while emphasizing that Islamic principles continue to serve as a foundation for family life.